2013
DOI: 10.3348/kjr.2013.14.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endobronchial Marginal Zone B-Cell Lymphoma of Bronchus-Associated Lymphoid Tissue: CT Findings in 7 Patients

Abstract: ObjectiveTo investigate CT and 18F-flurodeoxyglucose (18F-FDG) positron-emission tomography/CT findings of primary endobronchial marginal zone B-cell lymphoma of the bronchus-associated lymphoid tissue (BALT).Materials and MethodsFrom June 2006 through April 2012, seven patients (six female, one male; age range, 21-61 years; mean age, 49 years) were examined who were pathologically diagnosed with the primary endobronchial marginal zone B-cell lymphoma of BALT. We evaluated the locations and characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 22 publications
(30 reference statements)
3
31
1
3
Order By: Relevance
“…The pathogenic mechanisms of tracheal MALT lymphoma remain elusive, although it has been proposed that the disease is related to smoking, chronic inflammation, and autoimmune diseases [4, 5]. A Korean study reported that positron emission tomography-CT displayed some diagnostic merit for tracheal MALT lymphoma, with the maximum standardized uptake values ranging between 2.3 and 5.7 [6], which is consistent with our results. In addition, the study also reported that lesions of primary MALT lymphoma manifested no significant signal intensification in an enhanced CT scan, which clearly differed from our observation that some areas of the lesions did show an apparent enhancement.…”
Section: Discussionsupporting
confidence: 81%
“…The pathogenic mechanisms of tracheal MALT lymphoma remain elusive, although it has been proposed that the disease is related to smoking, chronic inflammation, and autoimmune diseases [4, 5]. A Korean study reported that positron emission tomography-CT displayed some diagnostic merit for tracheal MALT lymphoma, with the maximum standardized uptake values ranging between 2.3 and 5.7 [6], which is consistent with our results. In addition, the study also reported that lesions of primary MALT lymphoma manifested no significant signal intensification in an enhanced CT scan, which clearly differed from our observation that some areas of the lesions did show an apparent enhancement.…”
Section: Discussionsupporting
confidence: 81%
“…By reviewing titles and abstracts, 450 articles were excluded: 335 because they were not in the field of interest of this review; 20 because they were reviews, editorials or letters; 93 because they were case reports or small case series (less than five patients with MALT lymphoma); and two articles because they were not in the English language. Thus, 30 full‐text articles were assessed for eligibility . One additional study was found by screening the references of these articles .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 20 articles including 376 patients were selected and were eligible for the systematic review and meta‐analysis (Figure ). The characteristics of the included studies are presented in Tables .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations